Pencapaian Kemampuan Berpikir Geometri Tingkat Rendah Siswa: Analisis Berdasarkan Tipe Pembelajaran Kooperatif - Al Afgoni, Harun; Alghadari, Fiki; Vioreza, Niken (Pendidikan Matematika UNIMOR, 2020)
Two important elements in the learning process at school are how students' understanding and learning activities are. On the other hand, most students only memorize algorithmic formulas without understanding the concept in depth. As a result, students' thinking abilities at low levels become dominant in learning operations. This study was conducted with the aim of analyzing the achievement of students' low-level geometry thinking skills between the learning group of think pair share (TPS) and the two stay to stray (TSTS). This quantitative study was conducted on students in one of the junior high schools in the East Jakarta area. Data were obtained using instruments developed based on three initial levels of geometrical thinking according to van Hiele's theory. Data were analyzed with parametric statistics. The results of the data analysis concluded that there were differences in the achievement of the ability to think of low-level geometry students in the TPS and TSTS learning groups. Based on descriptive statistics, the average achievement of TPS group students is more than TSTS. According to the results of this study, learning the geometry of the triangle concept for junior high school students is suggested by learning TPS. There are indications based on the distribution of data that the level of thinking of students in geometry is mostly at the level of analysis.